Possible vertebral brucellosis infection in a Neanderthal - Bruce Rothschild; Martin Haeusler (Scientific Reports, 2021)
Abstract The La Chapelle-aux-Saints 1 skeleton of an old (>60-year-old) male Neanderthal is renowned for the advanced osteoarthritis of its spinal column and hip joint, and their implications for posture and lifestyle in these Mid- to Late Pleistocene humans. Reassessment of the pathologic lesions reveals erosions at multiple non-contiguous vertebrae and reactive bone formation extending far beyond the left hip joint, which suggests the additional diagnosis of brucellosis. This implies the earliest secure evidence of this zoonotic disease in hominin evolution. Brucellosis might have been transmitted via butchering or eating raw meat and is well compatible with the range of prey animals documented for Neanderthals. The associated infertility could have represented an important aspect of health in these late archaic humans.